Highly Anisotropic Fluorine‐Based Plasma Etching of Ultralow Expansion Glass. Issue 6 (11th March 2021) - Weigel, Christoph; Phi, Hai Binh; Denissel, Felix Arthur; Hoffmann, Martin; Sinzinger, Stefan; Strehle, Steffen
Abstract : Deep etching of glass and glass ceramics is far more challenging than silicon etching. For thermally insensitive microelectromechanical and microoptical systems, zero‐expansion materials such as Zerodur or ultralow expansion (ULE) glass are intriguing. In contrast to Zerodur that exhibits a complex glass network composition, ULE glass consists of only two components, namely, TiO2 and SiO2 . This fact is highly beneficial for plasma etching. Herein, a deep fluorine‐based etching process for ULE 7972 glass is shown for the first time that yields an etch rate of up to 425 nm min −1 while still achieving vertical sidewall angles of 87°. The process offers a selectivity of almost 20 with respect to a nickel hard mask and is overall comparable with fused silica. The chemical surface composition is additionally investigated to elucidate the etching process and the impact of the tool configuration in comparison with previously published etching results achieved in Zerodur. Therefore, deep and narrow trenches can be etched in ULE glass with high anisotropy, which supports a prospective implementation of ULE glass microstructures, for instance, in metrology and miniaturized precision applications. Abstract : Highly anisotropic plasma structuring of ultralow thermal expansion glass (ULE 7972), as an alternative to the far more complex material Zerodur, is investigated. Based on the composition, the material structure, and the plasma parameters, high aspect ratios and nearly vertical sidewalls are achieved. This enables the use of ULE 7972 in high precision and temperature‐stabilized microsystems.